Evaluation of the influence of climatic and geomorphological factors on landslides development - Kovrov, Oleksandr; Kolesnik, Valerij; Buchavyi, Yurii (ІТГІП, 2018)
The paper deals with the study of factors influencing the propagation of landslides in Ukraine. According to numerous monitoring studies, climate changes have significant impact on the stability of natural slopes and cause landslide processes. The topicality of the study is connected with the multifactor mechanism of landslides formation and complexity of this process development in space and time scales. Activation of landslides is registered on the territory of almost all administrative regions of Ukraine. The increasing dependence of the number of recorded landslides on annual precipitation and relief is established. For the most landslide-prone regions of Ukraine, the integral coefficients of the relief influence have been calculated, and the levels of potential landslide risk have been determined. Linear regression dependence between the amount of atmospheric precipitation and the number of landslides has been obtained, which allows predict landslide hazard in the regions of Ukraine. The results of the calculations are presented graphically in the form of a map.
Keywords: exogenous geological processes; landslide; model of global circulation; integral coefficient of the relief influence; landslide risk; 624.131.31551.4]:551.56